Education and its effects on the labour market in Macedonia. - Cvetanoska, Marijana; Trpeski, Predrag (Faculty of Economics Pale, 2019)
Human capital represents the most valuable asset held by most individuals. Peopleaccumulate human capital through investments in schooling and training. Governments subsidizemany forms of human capital accumulation including primary, secondary and post-secondaryschooling.Education plays a central role in preparing people to enter the labour market, offering themthe opportunity to improve and increase their knowledge, skills and abilities. In recent decades, therehas been rapid expansion of higher education across many countries. This has had important andprofound effects on labour markets and the way in which employers use highly educated labour.Thelevel of education is one of the key predictors of long-term success in the labour market, it is related tothe likelihood to be employed, the amount of salary and the quality and social attractiveness of the job.Therefore, the aim of this study is to identify and analyze the relationship that exists betweeneducation and labour market in Macedonia. In order to reach this aim, information included in thestatistical yearbooks (secondary data), reports and in different researches that have been made indifferent countries are analyzed and interpreted. This study provided evidence for the positive effectsof education on the labour market in Macedonia. There is a positive link between the level ofeducation and access to work and another positive effect of education on the labour market is relatedto the level of income.
Keywords: education, human capital, labour market, Macedonia